Implementation of EVE-NG in Increasing the Effectiveness of Project-Based Learning in the Network Computer Engineering Technology Study Program - Utomo, Hendrik Setyo; Sholeha, Eka Wahyu; Supriyanto, Arif; Rusmana, Deni; Majid, Al (Brilliance: Research of Artificial Intelligence, 2024)
The increasing demand for practical skills in computer networks has made hands-on learning a crucial element in information technology education. This study focuses on evaluating the usability of EVE-NG, a network simulation platform, to optimize project-based learning for students in the Computer Engineering and Network Program (TRKJ) at Politeknik Negeri Tanah Laut. The students, in their third semester, were selected as respondents, as they were enrolled in the Computer Networks 3 course, which is relevant to the practical use of EVE-NG. A usability analysis was conducted using five key indicators: Learnability, Memorability, Efficiency, Errors, and Satisfaction, assessed through questionnaires. The findings revealed that EVE-NG performs adequately across all indicators, with average scores ranging from 2.82 to 3.04, indicating good usability overall. Learnability and Memorability were rated as "good," though some users reported challenges in adapting to certain interface elements. Efficiency was rated "fair," with some feedback highlighting the need to improve workflow speed. The Errors indicator showed relatively low user mistakes, suggesting that the system is generally intuitive, although some interface ambiguities remain. Satisfaction received the highest score, reflecting user contentment with the platform, though improvements in system speed and interface clarity were suggested. The results provide essential insights into the current usability of EVE-NG and offer recommendations for further enhancements. With targeted improvements, EVE-NG can offer a more efficient and user-friendly experience, better supporting practical, real-world network simulation tasks in educational settings.